A general strategy for synthesizing colloidal semiconductor zinc chalcogenide quantum rods - Jia, Guohua; Banin, U. (American Chemical Society, 2014)
Quasi-one-dimensional (1D) semiconductor nanocrystals manifest linearly polarized emission, reduced lasing threshold, and improved charge transport compared with their counterparts such as spherical quantum dots. Present investigations of colloidal semiconductor quantum rods are mainly based on cadmium chalcogenide systems because of their facile synthetic accessibility. However, it is still a big challenge to fabricate quasi-1D zinc chalcogenide nanocrystals with controlled aspect ratios. Here we report a general strategy for synthesizing zinc chalcogenide quantum rods via a colloidal chemical synthetic approach. Unlike the most common growth mechanisms of quasi-1D colloidal nanocrystals such as monomer attachment and particle coalescence, the synthesis of zinc chalcogenide quantum rods is performed by a ripening process starting from their respective ultrathin nanowires through thermodynamically driven material diffusion. We anticipate that this strategy is general and could be applied to other systems to construct quasi-1D nanostructures. Moreover, the presence of cadmium-free (or "green") zinc chalcogenide quantum rods synthesized through this strategy provides a desirable platform for eco-friendly photocatalysis, optoelectronic devices, biolabeling, and other applications.